Double intestinal duplication and incidental neuroendocrine tumor of appendix, a rare case of acute abdomen. (2015) - Bellanova, G.; Valduga, P.; Costa, A.; Barbareschi, M.; De Carli, N.; Giannelli, G.; Di Sipio, A.; Prezzi, C.; Ciarleglio, F.A.; Beltempo, P.; Marcucci, S.; Giacomin, D.; et al.
Highlights: We present a rare case of double intestinal duplication and incidental neuroendocrine tumor of appendix like acute abdomen. We discuss about the difficult in diagnostic imaging. We consider surgery mandatory for diagnosis and definitive therapy in these cases. Abstract: Introduction: Intestinal duplication is rarely reported in adulthood and often remains undiagnosed until onset of complications. We describe the case of a 39 year old woman who came to our observation for acute abdomen due to a combination of double intestinal duplication (colon and ileum) and an incidental neuroendocrine tumor of the appendix. Materials and methods: A 39 year old woman who was admitted at with upper abdominal pain. Multisliced spiral CT scan showed a cystic lesion suggestive of an inflammed Meckel's diverticulum.The patient was underwent an urgent explorative laparoscopy. The intraoperative findings revealed a cystic lesion of the anti-mesenteric side of transverse colon, apparently dissectable from the bowel and a second lesion with a strongly adherent and unresectable from the anti-mesenteric aspect of the small bowel. A combined appendectomy was also performed. The histological diagnosis was consistent with a typical intestinal duplication for both intestinal lesionsand an incidental 2 mm carcinoid tumor was also found in the appendix. The postoperative course was uneventful and the patient was discharged on p.o. day 5. At the presenttime she is well and following a regular oncologic follow-up. Discussion: The rarity of this case is due to the concomitant presence of an incidental, sincronous, appendiceal NET. The elective treatment is surgical resection. Conclusion: Intestinal duplication in the adulthood is extremely rare and may either have an acute presentation as acute abdomen or represents an incidental finding of mass. We suggest that, once the diagnosis is suspected patient must undergo surgery.